Large eddy simulation on wind-induced interference effects of staggered chamfered square cylinders - Wenlong Cao; Xueyan Wang; Yubo Liu; Yujie Yin; Jian Yang; Jianhui An (Scientific Reports, 2023)
Abstract Chamfered corners in buildings are the main means to reduce the control effect of wind load on the structure, and the interference effect of chamfered buildings cannot be ignored. At present, only the mutual interference coefficients of square and rectangular section buildings are given in the Chinese code, without the interference effect of chamfered buildings being specified. Therefore, in this paper, aerodynamic force and wind pressure coefficients of chamfered square cylinders of different spacing are obtained by the large eddy simulation method. Wind load characteristics, non-Gaussian characteristics and interference effects of chamfered square cylinders with different arrangements are studied based on aerodynamic coefficients, wind pressure coefficients and interference coefficients. The results show that when the wall y plus value is 1, the large eddy simulation is the most accurate to simulate the wind load and wind field parameters. Besides, the aerodynamic effects, non-Gaussian characteristics and interference effects between the chamfered square cylinders are mainly controlled by the cross-wind interval and the spacing (4.0, 4.0) is the characteristic coordinate. That means, when the spacing is smaller than this coordinate, the interference effect of the square cylinder is more obvious. When the spacing coordinate is greater than (4.0, 4.0), the aerodynamic coefficients and non-Gaussian regional distributions of the principal square cylinder and the isolated cylinder are the same, and the interference factor approaches 1.